Analisis Rasio Likuiditas dalam Mengidentifikasi Potensi Kepailitan dan Proses Likuidasi Bertahap pada PT. Sri Rejeki Isman Tbk. pada Tahun 2023 - Laras Ayu Wulandari; Rohmah Dani Andikasari; Nasywa Salma Najmi; Zarfina Fitri Aisyah; Endang Kartini Panggiarti (Indonesia Economic Journal, 2026)
The purpose of this study is to analyze liquidity ratios to identify the potential for bankruptcy and the gradual liquidation process of PT Sritex in 2023. The method used is descriptive qualitative, using a financial ratio analysis approach (current ratio, quick ratio, cash ratio) in Sritex's 2023 annual financial report. The results show that the current ratio (1.74) and quick ratio (1.11) are still above 1, but the cash ratio is only 0.02, indicating very severe liquidity, indicating that the company is experiencing severe financial pressure, leading to financial distress and bankruptcy as a long-term impact. The court declared PT Sritex bankrupt in October 2024. The gradual liquidation process was then carried out by the curator through pre-liquidation, initial liquidation, and advanced liquidation stages. In conclusion, a low cash ratio and capital deficiency are accurate indicators of potential bankruptcy